The relation between corporate financing activities, analysts’ forecasts and stock returns - Bradshaw, Mark T.; Richardson, Scott A.; Sloan, Richard G. (Journal of Accounting and Economics, 2006)
We develop a comprehensive and parsimonious measure of corporate financing activities and document a negative relation between this measure and both future stock returns and future profitability. The economic and statistical significance of our results is stronger than in previous research focusing on individual categories of corporate financing activities. To discriminate between risk versus misvaluation as explanations for this relation, we analyze the association between our measure of external financing and sell-side analysts’ forecasts. Consistent with the misvaluation explanation, our measure of external financing is positively related to overoptimism in analysts’ forecasts.